ANALYSIS OF ECO ENZYME CHARACTERISTICS WITH VARIATION OF “TAPE” YEAST CONCENTRATIONS - Karimah, Miftahul; Lusiani, Cucuk Evi (Politeknik Negeri Malang, 2024)
Eco enzyme is a multipurpose liquid which produced from organic waste. The liquid made with the ratio of raw materials in the form of brown sugar: organic waste: water is 1:3:10 which is processed using a fermentation process for 90 days. One method to shorten the fermentation time is adding yeast as catalyst throughout the fermentation process. This research aims to analyze the characteristics of the eco enzyme with variations in “tape” yeast concentrations. Raw material used in this research included organic waste (orange and melon peels with a ratio of 1:1), brown sugar, water, and “tape” yeast (yeast concentrations of 1, 2, 3, 4 and 5%w/v) through fermentation process for ten days. The eco enzyme products were tested to determine the pH value, TDS value, acetic acid content, aroma, color and protease enzyme activity. The analysis results showed that the pH value of eco enzyme products was in the range of 3.9 to 4.1, TDS (Total Dissolved Solids) value of 1339 to 1405 ppm, acetic acid content of 0.81 to 1.08%w/w, had bright yellow and deep yellow color with a fermented aroma. The selected eco enzyme product in this research was on eco enzyme with yeast concentration of 3 %w/v which had pH value of 3.9 TDS value 1403 ppm, acetic acid content of 0.81%w/w, and the color was bright yellow with fermented aroma. However, there was no clear zone around the colony in the test indicating that there was no protease enzyme activity.